Effect of Different Treatments on Nutritional, Microbiological and Rheological Properties of Flours : Effect of different treatments on properties of flours - Munir, Neelma; Riaz, Armish; Saba Ghulam Mustafa; haq, Rukhama; Ilyas, Saiqa; Naz, Shagufta (Progress in Nutrition, 2021)
Among the different types of flours wheat flour, gram flour are commonly used. Wheat flour is a leading source of cereal protein having the higher protein content than either rice or maize (corn). Semolina is very popular food product made by milling wheat. It is a rich source of Carbohydrates, Iron and Protein and is widely used worldwide for making pasta, cereals and spaghetti etc. Gram flour or chickpea flour is an important pulse flour and a rich source of protein and carbohydrates. Present study was carried out to study the effect of gamma radiation, microwave radiation and ETO treatment on the nutritional, microbiological and solubility properties of different flours i.e. wheat flour, gram flour and semolina. In the present study flour samples were exposed to 5KGy Gamma radiation, 900W (for 40s) Microwave radiation and ETO treatment. The nutritional value of samples after different radiation treatments was analyzed to determine the change in proximate composition. Through experimentation, it was evaluated that there was no significant difference in the nutritional characteristics of flours after being exposed to different radiations. Microbial bioburden of flours was reduced significantly after treatment with different radiations specifically by treatment with gamma radiation and microwave radiation. However, treatment with microwave radiation resulted in loss of some sensory characteristics. While ETO treated flour, samples showed more microbial growth than other types of radiations. Therefore, gamma radiation is the most promising technique to ensure food safety with no significant change in the sensory and nutritional properties of flours.